Financial Hardship and Its Correlation with Teacher Professionalism in Rural Primary Schools of Modoinding - Welky Karauwan; James Ed. Lalira; Rose Marie Lolowang; Rieneke Ryke Kalalo; Sjerly Maria Lumi; Theo Chanra Merentek (SOSIOEDUKASI, 2025)
This study aims to provide an overview of the professionalism of elementary school teachers, the relationship between economic burdens and the level of teacher professionalism, and what economic burdens are wrapped around and most wrapped around teachers in rural areas located in the Modoinding sub-district, South Minahasa district, North Sulawesi, Indonesia. This research uses a descriptive qualitative method. A total of 92 teachers were selected as the sample of this study varying between levels D-II, D-III, and D-IV/S1. In-depth interviews were conducted in this study, and the identification results found that 30 teachers belonged to class IIIa with working periods varying between 10 to 16 years and a salary range between IDR.3,252,900 to IDR.3,570,100. The research results found several types of financial burdens experienced by teachers, and the most wrapped around them are limited salaries, incentives, and debt. It showed that instructors deal with a variety of financial difficulties, the most common being inadequate pay, little incentives, and excessive debt. Their inability to pay for necessities is hampered by these financial difficulties, which also have a negative effect on their concentration and commitment to their work-related obligations. Particularly when it comes to debt, teachers are frequently compelled to look for other means of money, which takes them away from their core responsibility as educators. As a result, these financial constraints may have a negative impact on the standard of instruction underscoring the need for more focused interventions to address these problems.